PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA, DAN KEDISIPLINAN TERHADAP KINERJA KARYAWAN : (Studi pada PT. Indosat Persero Tbk Gerai Indosat Ooredo Hutchison Solo) - Anggi Patricia Anindya Carolin Suparming; endang winarsih; Dwinda Agustintia (ITB AAS Indonesia Surakarta, 2025)
The Purpose Of This Research Is To Know The Effect Of Leadership Style, Work Environment, And Discipline On Employee Performance. The Scope Of This Research Was Conducted On Employees Of Pt Indosat Persero Tbk Solo Using A Survey Method. This Survey Was Chosen Because Sampling Would Be More Efficient. The Population In This Study Were Employees Who Worked At Pt Indosat Persero Tbk Solo Consisting Of 50 Employees Who Worked At Pt Indosat Persero Tbk Solo. The Sampling Technique In This Study Was Boring Sampling Or Total Sampling. The Sample In This Company Amounted To 50. Data Collection Techniques Used In This Study Were Questionnaires And Personal Interviews. The Definition Of Operational Research Variables Included Leadership Style, Work Environment, Work Discipline And Employee Performance. Data Analysis Techniques Used Classical Assumption Tests, Multiple Linear Regression Analysis, T Test, F Test, And Determination Test. Keywords : Leadership Style, Work Environment, Work Discipline, Employee Performance